Analisis PPh Pasal 21 dan Dampak Perubahan PTKP pada PT Pelabuhan Indonesia I (Persero) Medan - Destari Nurlaila Damanik (Jurnal Riset Akuntansi dan Bisnis, 2021)
This research was conducted to find out the imposition of PTKP (Non-Taxable Income) rates used by the company also aimed to analyze the calculation of Income Tax Article 21 applied to PT. Pelabuhan Indonesia I (Persero) Medan and adjusting it to the Tax Law and Regulations on Income Tax Article 21 latest. This research approach is descriptive research while data collection techniques are carried out with documentation studies. The data analysis technique in this study is a descriptive method that is by collecting data in the form of company records or reports related to employee payrolls, analyzing the calculation of Income Tax Article 21 and adjusting to the Tax Law or Tax Regulations in 2019, concluded the results of the study. The results of research conducted on PT. Pelabuhan Indonesia I (Persero) Medan shows that the calculation of Income Tax Article 21 on the salaries of permanent employees is not in accordance with the Regulation of the Minister of Finance No.101 / PMK.010 / 2019 concerning the adjustment of the amount of Non-Taxable Income.